A Data-Driven Traffic Steering Algorithm for Optimizing User Experience in Multi-Tier LTE Networks - Gijón, Carolina; Toril-Genovés, Matías; Luna-Ramírez, Salvador; Marí-Altozano, María Luisa (IEEE, 2019)
Multi-tier cellular networks are a cost-effective solution for capacity enhancement in urban scenarios. In these networks, effective mobility strategies are required to assign users to the most adequate layer. In this paper, a data-driven self-tuning algorithm for traffic steering is proposed to improve the overall Quality of Experience (QoE) in multi-carrier Long Term Evolution (LTE) networks. Traffic steering is achieved by changing Reference Signal Received Quality (RSRQ)-based inter-frequency handover margins. Unlike classical approaches considering cell-aggregated counters to drive the tuning process, the proposed algorithm relies on a novel indicator, derived from connection traces, showing the impact of handovers on user QoE. Method assessment is carried out in a dynamic system-level simulator implementing a real multicarrier LTE scenario. Results show that the proposed algorithm significantly improves QoE figures obtained with classical load balancing techniques.
Keywords: Sistemas de comunicaciones inalámbricos; Mobile network; Quality of Experience; Self- Organizing Network; Reference Signal Received Quality; load balancing